2022
DOI: 10.1128/aac.00284-22
|View full text |Cite
|
Sign up to set email alerts
|

Drug Repurposing in Chagas Disease: Chloroquine Potentiates Benznidazole Activity against Trypanosoma cruzi In Vitro and In Vivo

Abstract: Drug combinations and drug repurposing have emerged as promising strategies to develop novel treatments for infectious diseases, including Chagas disease. In this study, we aimed to investigate whether the repurposed drugs chloroquine (CQ) and colchicine (COL), known to inhibit Trypanosoma cruzi infection in host cells, could boost the anti- T. cruzi effect of the trypanocidal drug benznidazole (BZN), increasing its therapeutic efficacy while reducing the dose ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 62 publications
0
7
0
Order By: Relevance
“…As a perspective, it would be interesting to evaluate the parameters in a more advanced chronic stage of ChD, in which it would be possible to analyze the drug’s effect in the long term. On the other hand, nitazoxanide could be used in combination with benznidazole to improve its trypanocidal effectiveness, as noted by several authors when combining different drugs with benznidazole [ 22 , 23 , 31 , 43 , 44 , 45 , 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…As a perspective, it would be interesting to evaluate the parameters in a more advanced chronic stage of ChD, in which it would be possible to analyze the drug’s effect in the long term. On the other hand, nitazoxanide could be used in combination with benznidazole to improve its trypanocidal effectiveness, as noted by several authors when combining different drugs with benznidazole [ 22 , 23 , 31 , 43 , 44 , 45 , 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…42 In addition, factors such as age, geographic distribution, the immune background of the host and the natural resistance of some strains of T. cruzi to the drug can affect the effectiveness of the treatment. [43][44][45] In this context, we sought to evaluate the cytokine profile in observed in a prospective cohort study where a significant reduction in parasitemia, lower prevalence of markers of severe cardiomyopathy and lower mortality after 2 years of follow-up of patients with chronic Chagas disease who received at least one cycle of BZ treatment. 53 BZ is a relevant drug in immunomodulatory changes, although it has many negative points, such as its use in chronic patients with cardiac dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…The efficacy of the available drugs BZ and Nifurtimox is low in the chronic phase of Chagas disease, the phase in which most patients are diagnosed, and there are frequent side effects 42 . In addition, factors such as age, geographic distribution, the immune background of the host and the natural resistance of some strains of T. cruzi to the drug can affect the effectiveness of the treatment 43–45 …”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that chloroquine, hydroxychloroquine [23], and primaquine [24] have activity against different species of Leishmania. Moreover, chloroquine also showed improved activity when used together with benznidazole, the standard treatment against Trypanosoma cruzi [25]. On the other hand, insecticides used for vector elimination have also been tested against some parasites, sometimes obtaining activity against kinetoplastids [26], although this is a complex field due to parasite adaptations.…”
Section: Discussionmentioning
confidence: 99%